Effects of low glycemic index dietary intervention in women with Gestational Diabetes Mellitus - Ahmad Shuhaimi, Farhanah (2015)
High maternal glycemia especially at the postprandial level have been associated with high rates of complications in women with Gestational Diabetes Mellitus (GDM). A low glycemic index (LGI) diet may offer some benefits since the LGI foods usually produce lower postprandial blood glucose (PPG) responses as compared to high GI (HGI) foods. This randomized controlled study was conducted to investigate the effect of a LGI diet on glycemic-related parameters, other metabolic responses and dietary intake in women with GDM. A total of 40 participants (aged 32 years; mean ± SD pre-pregnancy Body Mass Index (BMI) 29.3 kg/m2 ± 7.3; mean ± SD gestation age = 26 week ± 3.5) from Universiti Kebangsaan Malaysia Medical Centre (UKMMC) were randomized to either LGI group (n=20) or Standard Nutrition Therapy (SNT) (n=20) groups to receive intensive intervention in which the outcomes were measured after 4-weeks period. As part of the study, the acute study was performed at week 1, 2 and 4 to determine the acute effects of LGI and HGI meal on postprandial metabolic responses (at week 1 and 2) and to challenge the postprandial response after having intensive intervention at week 4. At baseline, participants in both groups were homogenous. At 4 weeks, both groups reduced the fructosamine levels (p<0.05) with no different detected between group. LGI intervention had significantly better reduction on selfmonitoring blood glucose (SMBG) at 1-hour post breakfast by 11.8% recorded at home than the participants in the SNT group (p<0.05). No significant different were reported in lipid profile and C- Reactive Protein (CRP) between both groups after the 4 weeks of intensive intervention. Dietary Glycemic Index (GI) of participants in LGI group was significant lower by 7 units than SNT group (p<0.05). In the acute study, the 3-hours PPG was significantly lower after consuming low glycemic index meal (LGI_M) than the high glycemic index meal (HGI_M). The 4 weeks of LGI dietary intervention however, was not able to improve the PPG and triglyceride response after re-challenge with HGI_M at the end of the study. In conclusion, LGI dietary intervention was able to improve SMBG at 1-hour post breakfast. A LGI diet was feasible in this study, as the dietary GI in LGI group has reduced significantly at the end of the study. The improvement in PPG was also evident after having LGI meals as compared to HGI meals in women with GDM.